Visual and Performing Arts for National Development (FULAFIA IAC Book of Proceedings, 2024)
The paper "Visual and Performing Arts for National Development" examines the pivotal role of visual and performing arts in fostering national development. Drawing on existing literature and empirical evidence, this paper explores how the arts contribute to cultural preservation, economic growth, social cohesion, and individual empowerment within the context of national development strategies. Through a comprehensive analysis of the theoretical frameworks and practical implications, this paper underscores the importance of integrating visual and performing arts into broader development agendas. By leveraging the creative potential of artists and cultural practitioners, governments and policymakers can harness the transformative power of the arts to drive sustainable socio-economic progress and enrich the cultural fabric of society.